2021
DOI: 10.15190/d.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Transdiaphragmatic Intercostal Hernia- An Unusual Hepatic Injury After a Car Accident: A Case Report and Review of the Literature

Abstract: Transdiaphragmatic intercostal hernia, in which the abdominal contents of the hernia protrude through the diaphragm and the thoracic wall defect. is a very rare type of hernia with only a few cases having been reported in the literature. That type of hernia is usually manifested in male patients after trauma, penetrating or blunt. It is frequently presented with a palpable thoracic mass and pain. The indicated treatment is surgery. We present the case of a 60-year-old female admitted to the hospital after a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Ioannidis et al reported a female having blunt abdominal trauma resulting in a right-sided diaphragmatic injury and protrusion of the right lobe of the liver in the thoracic cavity along with a fracture of the right lower ribs [ 12 ]. Other unusual presentations may include other abdominal organs in the thorax, as seen in a case report of Daha et al in which a 24-year-old female with a right thoracic kidney with Bochdalek hernia was diagnosed incidentally [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ioannidis et al reported a female having blunt abdominal trauma resulting in a right-sided diaphragmatic injury and protrusion of the right lobe of the liver in the thoracic cavity along with a fracture of the right lower ribs [ 12 ]. Other unusual presentations may include other abdominal organs in the thorax, as seen in a case report of Daha et al in which a 24-year-old female with a right thoracic kidney with Bochdalek hernia was diagnosed incidentally [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several surgical options for the treatment of TDIH including primary closure, using mesh, and closure with prosthetic or autologous material [ 9 ]. In acute state of diaphragmatic hernia, primary repair of diaphragm is reasonable.…”
Section: Correspondencementioning
confidence: 99%